2013
DOI: 10.1002/pssb.201248392
|View full text |Cite
|
Sign up to set email alerts
|

Controlled manipulation of single atoms and small molecules using the scanning tunnelling microscope

Abstract: This article reviews manipulation of single molecules by scanning tunnelling microscopes, in particular vertical manipulation, lateral manipulation, and inelastic electron tunnelling (IET) manipulation. For a better understanding of these processes, we shortly review imaging by scanning tunnelling microscopy – as a prerequisite to detect the manipulated species and to verify the result of the manipulation – as well as scanning tunnelling spectroscopy and IET spectroscopy which are used to chemically identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 343 publications
(589 reference statements)
4
108
0
1
Order By: Relevance
“…Consequently, previous studies have addressed only complete or substantial fractions of monolayers. 18,19 Here we present now the results of the interaction among single [7]H molecules on Cu(111) at initial coverage. Upon cooling a low-coverage [7]H/Cu(111) sample to ∼6 K, molecular diffusion ceases and permits the direct observation of interacting [7]H molecules.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Consequently, previous studies have addressed only complete or substantial fractions of monolayers. 18,19 Here we present now the results of the interaction among single [7]H molecules on Cu(111) at initial coverage. Upon cooling a low-coverage [7]H/Cu(111) sample to ∼6 K, molecular diffusion ceases and permits the direct observation of interacting [7]H molecules.…”
mentioning
confidence: 94%
“…In order to study the interaction between two individual heptahelicene ( [7]H) molecules on a surface, sufficient mobility is required to facilitate pair formation. This suggests the use of noble metal substrates, which have relatively low adsorption energy.…”
mentioning
confidence: 99%
“…Towards this aim there has been a focus on using the tip of the scanning tunnelling microscope (STM) to induce atomic and molecular manipulation to build designer nano-structures with many striking results [5][6][7]. Underpinning these works are the ground-state properties of the target atoms and molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these advances are summarized in a number of recent reviews, and some of the highlights are shown in Figure 2. [31][32][33][34][35] The fundamental limitation of STM-based fabrication is that in many cases, it is limited to low temperatures, with liquid helium temperature (4 K) being the norm, and requiring atomically flat clean surfaces. These approaches are also fairly slow and have limited throughput.…”
Section: The Second Paradigm: Scanning Probe Manipulationmentioning
confidence: 99%